What to teach, when teaching economics as a minor subject? - Martin Kniepert (Universität für Bodenkultur Wien, Department für Wirtschafts- und Sozialwissenschaften, Institut für nachhaltige Wirtschaftsentwicklung, 2016)
Over the last few years, demands from student organisations for pluralism in teaching economics gave quite a stir to neoclassical economics; at least in the media, and at some selected universities. On the other hand, university teachers show considerable inertia. Sometimes they are pointing out that economic theory was not as streamlined as asserted. But mostly they insist on mainstream teaching as a basic prerequisite, possibly to be complemented later by some elective courses. While a dispute about the adequacy of this will certainly continue, it has to be stated that the typical syllabus for economics as a minor subject leaves the respective students with a very narrow notion of economics. This paper elaborates on this aspect. It outlines specific restrictions and requirements an economics-minor syllabus has to comply with in order to have a realistic chance for a wider dissemination at universities. Taking account of this, it is shown that pluralist intentions are covered to a considerable extent by the broader perspective of (new) institutional economics as developed by North, Williamson, Ostrom, and others. At the same time it allows for a coherent and commonly shared body of economic knowledge. To circumstantiate this, this paper resorts to important steps in the history of economic thinking, to its epistemological foundations, as well as to rather practical needs of mutual recognition of exams.
Keywords: A2; B0; B5; 330; Institutional Economics; economics-minor syllabus